Efficacy of curcumin and topical steroids in the treatment for oral submucous fibrosis: A comparative study - T A Deepak; M Manjunath; Harshita Thakur (Wolters Kluwer Medknow Publications, 2021)
Context: Oral submucous fibrosis (OSMF) is a chronic debilitating disease of the oral cavity, characterized by inflammation and progressive fibrosis of the submucosal tissues. The main agent involved in the pathogenesis of OSMF is areca nut. A wide range of treatment, including drug management, surgical therapy, and physiotherapy, has been attempted till date, with varying degrees of benefit. Aims: The objective of this study was to assess efficacy of curcumin for the treatment of OSMF; to asses efficacy of topical steroids for the treatment of OSMF; and to compare the efficacy of curcumin and topical steroid for the treatment of OSMF. Setting and Design: Participants were assessed based subjective and objective feature of OSMF, i.e., burning sensation of the oral cavity and interincisal distance, respectively. Methodology: Thirty participants were categorized into two groups: Group A was administered curcumin and Group B was administered topical steroids for a period of 3 months and followed up after 6 months. The assessment was based on maximal incisal opening and burning sensation for spicy food on Visual Analog Scale score. Analysis: Independent t test was applied for comparison within the group, ANOVA Bonferroni post hoc test was applied for multiple comparison of mean and Mann-Whitney U test was applied to compare the groups. Results: The statistical analysis revealed curcumin to be more efficient than topical steroid. Conclusion: The present study demonstrates the efficiency of curcumin and topical steroid to alleviate the clinical findings of OSMF. However, curcumin is comparatively more efficient than steroids for the treatment of OSMF.